Céphalées d’allure migraineuse révélatrice d’un accident vasculaire cérébrale sur dissection carotidienne - Andriamasinavalona, Rajaonarison Lala (Pan Afr Med J, 2017)
Dissections of cervicocephalic arteries are the main cause of stroke among the young adults. We report the case of a hypertensive and migrainous patient aged 59-years presenting with migrainous cephalea with flashes of light in his left eye and paroxysmal regressive paresthesia of the right hemicorpus. Clinical examination showed apraxia of speech associated with phonemic paraphasia. MRI of cerebral vascular territories with diffusion weighted imaging showed perivascular hyper-intense signal of the left internal carotid artery (intra-petrous portion) and T2 hyposignal suggesting hematoma in the wall with arterial occlusion at this level. MRI with diffusion and flair weighted imaging showed several ponctiform hyperintense signals at the level of the left anterior cerebral arterial territory and junctional hyperintense signals between the anterior cerebral artery and the middle cerebral artery without microbleeds at the level of the parenchyma, suggesting embolic stroke due to carotid dissection. The patient underwent curative Vitamin K antagonist anticoagulation treatment (target INR range of 2 to 3) after heparinotherapy with language therapy. At the three-month follow-up, angio MRI of the supra aortic trunk showed left intrapetrous internal carotid revascularization. Imaging plays an important role in the diagnostic confirmation of the dissections of cervicocephalic arteries and of possible stroke as well as in the immediate management and follow-up of patients.